ANALISIS KECURANGAN DI CABANG OLAHRAGA BADMINTON PADA AJANG SIRKUIT NASIONAL 2025 DI KEPULAUAN RIAU - Ibnu Sina; Tito Parta Wibowo; Rizki Rizkullah; Juang Maghribi; Nadya Rahayu; Muhamad Saeza (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study analyzes a cheating incident that occurred during the 2025 National Badminton Circuit (Sirnas) in the Riau Archipelago, where a young athlete was suspected of deliberately damaging the shuttlecock before serving. A qualitative method was employed through video analysis, semi-structured interviews with 10 stakeholders (athletes, referees, coaches), and a review of official documents. The findings reveal that the act of cheating was driven by competitive pressure, suboptimal referee oversight, and the athlete's mental fragility. The consequences included damage to the reputation of the athlete and their club, as well as a decline in public trust in the integrity of the sport. The discussion highlights the need for reforms in monitoring systems, enhanced character education, and strict sanctions by the Indonesian Badminton Association (PBSI). This study recommends the integration of instant replay technology and ethics-based simulation training to prevent recurrence.